Biotechnology DNA, to protein : - Thiel, Teresa (McGraw-Hill, 2001)
This one-semester, project-based laboratory manual gives junior/senior level students the opportunity to characterize the enzyme alpha-amylase. As students proceed through the sequenced experiments, they will learn the principles of DNA, RNA, and protein structure by using modern-day laboratory techniques. Genetics, cell biology, and organic chemistry are prerequisites.